Fetomaternal Outcome in Females with Hepatitis Virus - Uzma Yaqoob, Asif Hanif, Sadaf Ghulam Rasool, Tahira Ashraf, Fatima Tu Zahra, Sajida Parveen, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was designed to see fetomaternal outcome in pregnant females with hepatitis virus infection. Methodology: This cross sectional study was designed at Lady Atchison hospital Lahore from March 2015 to September 2015. Using nonprobability purposive sampling, we enrolled 104 cases with hepatitis virus infection, in which 80(76.9%) cases had HCV and 24(23.1%) had Hepatitis B virus. Pregnant females 18-40 years old with gestational age > 24 weeks (on dating scan), having any parity with positive diagnosis of HCV or HBV through Eliza were enrolled to see their fetomaternal outcome. The collected information was entered and analyzed in SPSS version 20. Results: The mean age of mothers was 27.35±4.339 years and mean gestational age at time of delivery was 36.1±3.51 weeks with minimum and maximum of 27 and 41 weeks. The mean birth weight was 2.792 ±1.41 kg whereas the mean APGAR score was 6.56±1.92 at 6 minutes. Intrauterine Deaths were observed in 10(9.6%) women. Preterm labour was seen in 24(23.1%) women. Fetal distress was found in 36 (34.6%) women. Emergency C section was done for 72 (30.8%) women. Postpartum haemorrhage was seen in 2 (1.9%) women. A total of 34 (32.7%) premature babies were born. Conslusion: Pregnant females with hepatitis infection had increased risk of intrauterine death, fetal distress and emergency caesarean delivery. Moreover, high percentage of low birth weight, pre-mature births and preterm labour was also observed.